Immunohistochemical Expression of Antioxidant Enzyme PRDX6 in Oral Squamous Cell Carcinoma In Relation to Clinicopathological Parameters - Mustafa Gheni Taher; Wasan Hamdi Younis; Muna Salih Merza (Diyala Journal of Medicine, 2018)
Background:The PRDX6 antioxidant family is important in the protection of cells against oxidants in humans. It is encoded by the PRDX6 gene. Peroxiredoxin 6 antioxidant enzyme (PRDX 6) has been reported in several cancers. However, the function of PRDX 6 in oral squamous cell carcinoma (OSCC),is far from being understood.